“Prayers from Him Who Is Unable to Make Offerings”: The Cult of Bēlet-ṣēri at Late Babylonian Uruk - Krul, Julia (Journal of ancient Near Eastern religions, 2018)
After 484 BC, several deities were (re)introduced into the pantheon of Uruk—most importantly the city’s new patron deity, the sky god Anu, but also the netherworld goddess Bēlet-ṣēri (“Lady of the Steppe”). In this article, I investigate the possible reasons behind the introduction of Bēlet-ṣēri’s cult at Uruk and the role ascribed to her by local worshipers. Using literary compositions, ritual texts, and legal documents, I trace the historical development of Bēlet-ṣēri’s divine characteristics, reconstruct her daily worship at Uruk, and examine the socioeconomic status of Urukean individuals bearing a “Bēlet-ṣēri-name.” I conclude that Bēlet-ṣēri was especially popular among non-elite citizens, probably because she could intercede with the queen of the netherworld, Ereškigal, for the lives of her followers and their families.